Motivasi Kepemimpinan Dalam Lembaga Pendidikan - Akhli Nur Mubiarto; Syarifuddin Syarifuddin (Al-Khair Journal: Management Education, 2021)
Abstract: Motivation in educational institutions is very important, because every personnel or employee member definitely needs a motivation, both from within himself and from others, for that if someone is already motivated or motivated, that person's performance will increase so that he can achieve a goal. Motivation is needed because with this motivation it is expected that everyone can work hard and be enthusiastic to achieve high work productivity. The purpose of this study is to determine the motivation of leadership in educational institutions and the relationship between leadership and educational institutions. This study uses a qualitative descriptive method with a literature study approach by collecting various references. In general, leadership can be understood as a leader who is able to direct, foster or regulate, guide and also show or influence. And educational institutions are a useful forum for fostering human beings, leading to a better future. Leadership in educational institutions can be referred to as someone who holds the authority that determines the development of educational institutions. As a professional educational leader, a leader is required to be able to make changes that are developmental and perfect.Keywords: Motivation, Leadership, and Educational Institutions Abstrak: Motivasi dalam lembaga pendidikan sangat penting, karena setiap personil atau anggota pegawai pasti memerlukan suatu motivasi, baik dari dalam diri pribadi maupun dari orang lain, untuk itu apabila seseorang sudah terdorong atau termotivasi maka kinerja seseorang itu akan meningkat sehingga dapat mencapai sebuah tujuan. Motivasi diperlukan karena dengan motivasi ini diharapkan setiap orang dapat bekerja keras dan bersemangat untuk mencapai produktivitas kerja yang tinggi. Tujuan dalam kajian ini untuk mengetahui motivasi kepemimpinan dalam lembaga pendidikan serta hubungan antar kepemimpinan terhadap lembaga pendidikan. Penelitian ini menggunakan metode deskritif kualitatif dengan pendekatan studi pustaka dengan mengumpumpulkan berbagai referensi. Secara umum kepemimpinan dapat dipahami sebagai pemimpin yang mampu mengarahkan, membina atau mengatur, menuntun dan juga menunjukkan ataupun mempengaruhi. Serta lembaga pendidikan adalah suatu wadah yang berguna untuk membina manusia, membawa kearah masa depan yang lebih baik. Kepemimpinan dalam lembaga pendidikan dapat disebut sebagai seseorang yang memegang otoritas yang menentukan perkembangan lembaga pendidikan. Sebagai pemimpin pendidikan yang profesional seorang pemimpin dituntut mampu melakukan perubahan yang bersifat pengembangan dan penyempurnaan.Kata Kunci: Motivasi, Kepemimpinan, dan Lembaga Pendidikan